Hepatic Arterial Infusion Chemotherapy Combined with Radiation Therapy for Advanced Hepatocellular Carcinoma with Tumor Thrombosis of the Main Trunk or Bilobar of the Portal Vein - Yumi Kosaka; Tomoki Kimura; Tomokazu Kawaoka; Yutaro Ogawa; Kei Amioka; Kensuke Naruto; Yuki Yoshikawa; Chihiro Kikukawa; Yosuke Suehiro; Kenji Yamaoka; Yuwa Ando; Shinsuke Uchikawa; et al. (Liver Cancer, 2021)
Background: Overall survival of patients with advanced hepatocellular carcinoma (HCC) with Vp4 (tumor thrombosis of the main trunk or bilobar of the portal vein) is extremely poor. Purpose: The purpose of this study is to clarify the prognosis of hepatic arterial infusion chemotherapy (HAIC) combined with radiation therapy (RT) for advanced HCC with Vp4 and to analyze the factors that contribute to the prognosis. Methods: In this retrospective cohort study, 51 HCC patients who were treated with HAIC and RT for portal vein tumor thrombosis and met the following criteria were enrolled: (i) with Vp4; (ii) Child-Pugh score of 5–7; (iii) Eastern Cooperative Oncology Group performance status of 0 or 1; (iv) no history of systemic therapy; and (v) from September 2004 to April 2019. Results: Median overall survival and median progression-free survival were 12.1 and 4.2 months, respectively. Multivariate analysis showed >50% of relative tumor volume in the liver (HR, 3.027; p = 0.008) and extrahepatic spread with (HR, 3.773; p = 0.040) as signiﬁcant and independent factors of OS. The total overall response rate (ORR) was 19.6%; ORR in main tumor was 13.7%; and ORR in Vp4 was 51.0%. None of the patients who received HAIC combined with RT for advanced HCC with Vp4 developed hepatic failure. This combination therapy of HAIC with RT was safe and well tolerated in all cases. Conclusion: Combination therapies of HAIC and RT might be good therapy for advanced HCC with Vp4.